Reflection for learning in doctoral training: writing groups, academic writing proficiency and reflective practice. Issue 4 (4th July 2017) - Cahusac de Caux, Basil Khalifa Costas Derek; Lam, Cho Kwong Charlie; Lau, Ricky; Hoang, Cuong Huu; Pretorius, Lynette
Abstract: This literature review highlights the benefits of participating in a doctoral writing group, with specific emphasis on how these learning communities foster reflective practice skills development. In particular, this review proposes that the process of continuous peer feedback and discussion benefits students by helping them verbalise their internal reflective thinking, fostering reflective practice skills development through various authentic learning experiences. Consequently, this review highlights the importance of establishing and supporting doctoral writing groups to further develop doctoral students' personal epistemology, growth and professional practice.